1994
DOI: 10.1063/1.358508
|View full text |Cite
|
Sign up to set email alerts
|

Hole drift mobility measurements in amorphous silicon-carbon alloys

Abstract: Hole drift mobilities have been measured using photocarrier time-of-l-light for several hydrogenated amorphous silicon-carbon alloy specimens. We find that, as the band gap increases, the hole drift mobility remains essentially constant. The temperature and dispersion properties were broadly consistent with hole multiple trapping in the valence bandtail. In conjunction with previous drift mobility measurements in hydrogenated amorphous silicon-carbon alloys and hydrogenated amorphous silicon-germanium alloys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 9 publications
0
44
1
Order By: Relevance
“…1; L is the photocarrier displacement at the transit time ͑d / 2, if the entire sample is traversed͒, and E is the electric field ͑including an estimate of the effective, internal field͒. 7 The transit times were calculated using photocharge techniques 8,9 for the ratio L / E =7ϫ 10 −8 cm 2 / V. For reference, we show a multiple-trapping extrapolation of the hole drift mobility for one sample of a-Si: H; 10 it has not been feasible to directly measure D in a-Si: H for this value of L / E because of hole deep trapping by dangling bonds.…”
Section: Hole Drift-mobility Measurements In Microcrystalline Siliconmentioning
confidence: 99%
“…1; L is the photocarrier displacement at the transit time ͑d / 2, if the entire sample is traversed͒, and E is the electric field ͑including an estimate of the effective, internal field͒. 7 The transit times were calculated using photocharge techniques 8,9 for the ratio L / E =7ϫ 10 −8 cm 2 / V. For reference, we show a multiple-trapping extrapolation of the hole drift mobility for one sample of a-Si: H; 10 it has not been feasible to directly measure D in a-Si: H for this value of L / E because of hole deep trapping by dangling bonds.…”
Section: Hole Drift-mobility Measurements In Microcrystalline Siliconmentioning
confidence: 99%
“…However, the parameters were chosen so that the results can easily be adapted to hydrogenated amorphous silicon, for which DE V E48 me V [21,23]. The principal difficulty in applying the results from the last section is that the photogeneration in a solar cell is certainly not uniform, as was assumed; in this section we adapt the model to the case of solar illumination.…”
Section: Implications For Solar Conversion By Amorphous Siliconmentioning
confidence: 99%
“…These three parameters may be obtained from hole time-of-flight measurements such as the 1994 paper of Gu et al [23]. This paper proposed DE V =48 meV, m h 0 =0.27 cm 2 /V s, and an attempt-to-escape frequency n=7.7 Â 10 10 s; the product N V b T is equal to n. Unpublished work from Syracuse University [27] indicates that hole drift mobilities have increased in more modern samples, although no detailed description yet exists for how and why the three timeof-flight parameters vary in differing forms of a-Si:H. For simplicity, we use a valence band mobility m h 0 =1 cm 2 /V s and n=10 11 /s; the bandtail width is treated as a variable in the present work.…”
Section: Appendix D Solar Cell Modeling Parameters (With Valence Banmentioning
confidence: 99%
“…The empty dot is taken from Penchina (1965) in order to be consistent with the present data obtain by co-planar geometry. Please refer to Jiang, et al (1998) (Gu, et al, 1994) and for "triode" plasma deposited a Si:H from Electrotechnical Laboratory. The upper two regression lines represent the triodematerial; the open symbols represent prior measurements of Ganguly, et al (1996).____________________ 35 Fig.…”
Section: "High-field Electron-drift Measurements and The Mobilitymentioning
confidence: 99%
“…The hole mobilities are limited by trapping processes involving the valence bandtail. Remarkably, for the entire class of plasmadeposited amorphous silicon-germanium and amorphous silicon-carbon alloys deposited in "diode" reactors, representing many years of materials research, it has been found that the hole drift mobility remains nearly constant, with a best value of 2 × 10 -3 cm 2 /Vs under standard conditions (Gu, Wang, Schiff, Li, and Malone, 1994, and references therein).…”
Section: Introductionmentioning
confidence: 99%